2014
DOI: 10.1093/mnrasl/slu188
|View full text |Cite
|
Sign up to set email alerts
|

Mass-segregation trends in SDSS galaxy groups

Abstract: It has been shown that galaxy properties depend strongly on their host environment. In order to understand the relevant physical processes driving galaxy evolution it is important to study the observed properties of galaxies in different environments. Mass segregation in bound galaxy structures is an important indicator of evolutionary history and dynamical friction timescales. Using group catalogues derived from the Sloan Digital Sky Survey Data Release 7 (SDSS DR7) we investigate mass segregation trends in g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
32
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 39 publications
9
32
2
Order By: Relevance
“…At R ∼ 20 kpc (i.e., the smallest scales probed), the correction is 20-30 per cent and is negligible at R ∼ 50 kpc. We find that on average c t is approximately independent of cluster-centric distance, because there is no strong luminosity segregation of galaxies in clusters as massive as those in MENeaCS (e.g., Roberts et al 2015). For reference, a fraction of order 10 −6 lens-source pairs have |c t | > 0.01, which corresponds to the typical shear produced by massive cluster galaxies in our sample.…”
Section: Additive Shear Biasmentioning
confidence: 67%
“…At R ∼ 20 kpc (i.e., the smallest scales probed), the correction is 20-30 per cent and is negligible at R ∼ 50 kpc. We find that on average c t is approximately independent of cluster-centric distance, because there is no strong luminosity segregation of galaxies in clusters as massive as those in MENeaCS (e.g., Roberts et al 2015). For reference, a fraction of order 10 −6 lens-source pairs have |c t | > 0.01, which corresponds to the typical shear produced by massive cluster galaxies in our sample.…”
Section: Additive Shear Biasmentioning
confidence: 67%
“…We find with 99.1% confidence that the samples do not have the same radial distribution. The difference in central concentration may reflect mass segregation, with more massive galaxies in a cluster or group being more centrally concentrated (Presotto et al 2012;Roberts et al 2015). Plausible physical reasons for that apparent concentration range from environmentally dependent formation histories, differences in dynamical friction, or mass-dependent tidal stripping.…”
Section: The Ngc 2784 Galaxy Groupmentioning
confidence: 99%
“…Since the segregation results for the DM-halo masses of the galaxies are stronger when low mass galaxies are included, we wanted to determine if the lower mass cut would affect the stellar mass results in the same way. We compare our results to observational results from Roberts et al (2015), shown in black; while their sample is complete and unweighted in (a), it is Vmax weighted in (b) to correct for incompleteness. The mass limits on the host haloes are identical between our results and the observational results.…”
Section: Comparing Mz=0 and M Peakmentioning
confidence: 99%
“…The errors shown are standard errors on the mean. Note that we use r vir instead of R 200 and our positions are 3-D while those in Roberts et al (2015) are projected.…”
Section: Comparing Mz=0 and M Peakmentioning
confidence: 99%
See 1 more Smart Citation